The regulatory role of microRNAs in the development, cyclic changes, and cell differentiation of the hair follicle. (March 2022) - Mokabber, Haleh; Vatankhah, Mohammad Amin; Najafzadeh, Nowruz
Highlights: Dicer and Drosha-DGCR8 are expressed in the hair follicle. miRNAs and Dicer regulate epithelial-mesenchymal interactions during the development of hair follicles. miR-103, miR-15b, miR-17, miR-200b, miR-25, and miR-30c were also overexpressed during the anagen phase. miR-24, miR-125b, and miR-22 may synergistically function to promote hair regression. Abstract: A variety of studies have been evaluated the role of miRNAs in the development and cyclic changes of hair. It is well-documented that miRNAs play a vital role in the differentiation of hair follicle stem cells (HFSCs). Dicer and Drosha-DGCR8, the key components of microRNA biogenesis, were demonstrated to be expressed in the hair follicle (HF). Dicer has an essential role in the morphology and development of the anagen phase of hair. HF cycling is governed by miRNAs that regulate gene activation and silencing. MicroRNAs including miR-24, miR-125b, and miR-22 may synergistically promote hair regression. Other microRNAs, such as miR-148b can stimulate the Wnt/β-catenin signal pathway to enhance hair growth. Furthermore, some studies confirmed the important role of miRNAs in controlling the stemness and differentiation of HFSCs in vitro . Of note, studies are highlighting the role of other novel miRNAs in the biology of HF. Therefore, the present review aimed to investigate the importance of microRNAs in the control of HF biology in some species of mammals.